2019
DOI: 10.1002/smi.2854
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, social‐cultural values, life stress, and health behaviors in a national sample of adolescents

Abstract: Adolescence is a developmental period during which time individuals adopt health behaviors that affect their lifelong health and disease risk. Socioeconomic status, social–cultural values, and stress have all been hypothesized to play a role in this association, but very few studies have examined how these factors interrelate and explain differences in health behaviors in adolescence. To address this issue, we assessed youths’ socioeconomic status, social–cultural values, life stress levels across seven domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Stressed people may engage in health-risk behaviors such as unhealthy eating, smoking, and drinking alcohol. Risky-but often pleasurable-behaviors are ways to cope with stress [8][9][10][11][12][13]. A recent study conducted with Brazilian workers showed that high levels of perceived stress were associated with smoking, obesity, and the co-occurrence of health-risk behaviors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stressed people may engage in health-risk behaviors such as unhealthy eating, smoking, and drinking alcohol. Risky-but often pleasurable-behaviors are ways to cope with stress [8][9][10][11][12][13]. A recent study conducted with Brazilian workers showed that high levels of perceived stress were associated with smoking, obesity, and the co-occurrence of health-risk behaviors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, parental education, which was used as a proxy for socioeconomic status in this study, was not significant in any of the models. Socioeconomic status often plays a key role in individuals' health behaviors (Chen & Miller, 2013;Milas, Klaric, Malnar, Šupe-Domic, & Slavich, 2019;Nandi, Glymour, & Subramanian, 2014). It is likely that the homogeneous economic status of families from which our sample was drawn is the explanation for this unexpected result.…”
Section: Discussionmentioning
confidence: 86%
“…Data on 32,981 elderly people in Japan also found that both men and women of low SES were more likely to walk <30 min/day. This finding was true for 47.3% of men with <6 years of education compared with 33.9% of men with ≥13 years of education [33].…”
Section: Exercisementioning
confidence: 76%
“…Lower family income was associated with higher severe uncertainty stress (OR 1.25; 95% CI, 1.06-1.49) [32]. Both men and women with low SES were shown to experience more stress than those with high SES [33]. Second, people with low SES may be less knowledgeable with regard to information and resources for healthy behavior.…”
Section: Smokingmentioning
confidence: 98%
See 1 more Smart Citation